'Pessimo me, come padre': Paternity in Sanguineti and the Novecento tradition. Issue 1 (2nd January 2020) - O'Ceallachain, Eanna
This article investigates representations of paternity and the paternal self in the neo-avant-garde poetry of Edoardo Sanguineti, in the context of a poetic tradition dominated by filial perspectives. The article analyses the forms and emblematic functions of Sanguineti's paternal representations, and their cultural and ideological ramifications in the poetic context of the Italian Novecento. While existing scholarship has often discussed the recurrence of conjugal and broadly domestic themes as part of Sanguineti's representation of a social and corporeal io, this essay undertakes the first comprehensive analysis of how paternity specifically is constructed and used throughout his poetic works, from the 1950s to the early 2000s. After an initial survey of paternity in the works of some other Novecento poets, the article examines how Sanguineti's use of paternal motifs develops from the late 1950s onwards, both in his poetry and in the novel Capriccio italiano (1963), and how this reflects his ideological and aesthetic concerns, including a drive towards a demystificatory realism informed by his Marxian and Freudian perspectives. Throughout, Sanguineti writes fatherhood as primarily an embodied experience, anchored in a historicized present, lived and understood politically; while an increasing association between paternity and the death of the self culminates in the testamentary or post-mortem paternal postures of the 1980s. What emerges ultimately is a complex and contradictory construction of the paternal io as both a pathologically degraded self – one diminished in part by its own paternal status – and as a strong, sometimes patriarchal figure who leads and teaches the children, dispensing practical and ideological guidance: a gendered construction of a specifically masculine self whose representation brings together elements of both authority and abjection.